2000
DOI: 10.1007/s11908-000-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meningitis: Principles and practical aspects of therapy

Abstract: Acute bacterial meningitis continues to be associated with significant morbidity and mortality. Recent research efforts to improve outcome for such patients have focused on antibiotic-cerebrospinal fluid interactions, factors influencing antibiotic selection, indications for cranial imaging, the role of anti-inflammatory agents, and the impact of antibiotic timing on outcome. In this article, I use an illustrative case to review timely data on these topics and provide guidelines for the empiric and pathogen-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…Ampicillin remains the preferred drug for treatment of bacterial meningitis [22]. However, our present results showed that ampicillin in the early stage of treatment substantially worsen bacterial meningitis evidenced by the increases of mean CSF leukocyte counts and protein concentration.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Ampicillin remains the preferred drug for treatment of bacterial meningitis [22]. However, our present results showed that ampicillin in the early stage of treatment substantially worsen bacterial meningitis evidenced by the increases of mean CSF leukocyte counts and protein concentration.…”
Section: Discussioncontrasting
confidence: 49%
“…Acute bacterial meningitis can progress extremely fast and cause death within hours or days without appropriate diagnosis and treatment -so utmost caution is required [5,22]. Inflammation of bacterial meningitis is initiated by bacterial cell-wall constituents and cytotoxins in the subarachnoidal space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a rapid and accurate clinical evaluation is needed for the determination of risks due to meningitis [2] . Examination of cerebrospinal fl uid (CSF) is an important diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the pharmacodynamic properties of antimicrobials allows for appropriate optimization of bactericidal drug concentrations (Lutsar et al, 1998;Aronin, 2000). Bacterial killing is particularly important in the CSF in which there is a decreased immune response from relatively lower concentrations of antibody and complement and inefficient phagocytosis.…”
Section: Antimicrobial Pharmacodynamics In Csfmentioning
confidence: 99%